Тhe role of the internal use of mineral water in the complex treatment of patients with chronic viral hepatitis C with concomitant non-alcoholic fatty liver disease - Anna Izha (Kazimierz Wielki University, 2020)
Introduction: The use of modern drugs with direct antiviral effect allows achieving a stable virologic response (SVR) in patients with chronic hepatitis C (CHC). However, in most cases, after the elimination of HCV infection, the progression of fibrosis continues with the development of its terminal stages and adverse outcomes for patients. The presence of non-alcoholic fatty liver disease (NAFLD) in these patients significantly increases the rate of progression of fibrosis and its complications, even after reaching SVR. Therefore, the search and development of new non-drug treatment technologies for this category of patients is relevant. Aim: to study the effectiveness of mineral water intake (with a high content of bicarbonates, sodium, potassium, and silicon compounds) in the new mode of use in the complex treatment of patients with chronic hepatitis C with concomitant NAFLD. Methods: anamnestic, clinical, general clinical, biochemical (indicators of lipid metabolism, HOMA index), serological (markers of viral hepatitis C, HCV RNA PCR, qualitative and quantitative determination, genotyping), ultrasonographic studies of the digestive system and statistical methods. Results: Patients with chronic hepatitis C (genotype 1b in the phase of replication, minimal and moderate activity) with concomitant NAFLD, which had been divided into two groups, were examined. Patients of group I (control group) received a standard complex of treatment (diet therapy that corresponded to the Mediterranean diet, dosed exercise regimen, antiviral therapy - sofosbuvir (400 mg) and ledipasvir (90 mg) - 3 months). Patients of group II (the main group) additionally received an internal course intake of mineral water (MW) according to our methodology: 3 ml per kg of patient's body weight 30-40-60 min before meals, depending on the acidity in the stomach, and the same dose after food intake, three times a day (course - 2 months, a break - 2 months, a second course - 2 months). Evaluation of the effectiveness of treatment was carried out after six months from the start of treatment. Conclusion: The results prove the feasibility and effectiveness of using MW in a doubled dosage regimen in the complex treatment of patients with chronic hepatitis C with chronic concomitant NAFLD, which was determined by improving lipid metabolism, reducing signs of insulin resistance, improving ultrasonographic signs and preventing the development of fibrotic changes in the liver.